PENGEMBANGAN USAHA KATERING MENUJU INDUSTRI MIKRO BERDAYA SAING TINGGI - Sutiyoko; Suparni, Suparni; Munadi, Muhammad; Supriyadi, Nur Wahid (Abdi Masya, 2024)
The catering business is one of the businesses that is in great demand as a business opportunity. Bu Eny's catering was a food service business, especially snacks and packaged foods on a micro scale. This business was classified as a micro business because its annual sales have not reached IDR 300 million. Bu Eny Catering's biggest problem in serving consumers was the limited equipment to support the speed of the production process. Another problem was that marketing methods are still dominated by the dissemination of information via WhatsApp (WA) and mouth to mouth, there was no financial bookkeeping or purchasing of materials. The aim of this community service program was to assist Bu Eny's Catering in developing its business both in terms of facilities, marketing, as well as production and financial management. Method of catering assistance was planned in the form of increasing production speed, improving financial and production management, as well as marketing development. The results of this assistance were able to increase gross income by 4.1% and 16.5% in August and September 2023 respectively compared to July 2023. Production was more controlled with the production control board. Financial management was also more organized by using an income and expenditure book which was filled in every day. Marketing methods have been enhanced by the use of WhatsApp for business, but the impact cannot yet be measured. Based on the results of the mentoring program, the development of micro businesses to increase their competitiveness needs to be developed in many sectors. Micro-industry assistance has been proven to be able to increase its competitiveness amidst increasingly fierce competition in micro industries.